Beginning XML with DOM and Ajax From Novice to Professional - Jacobs, Sas (Apress : Imprint: Apress, 2006)
Don't waste time on 1,000-page tomes full of syntax; this book is all you need to get ahead in XML development. Renowned web developer Sas Jacobs presents an essential guide to XML. Beginning XML with DOM and Ajax is practical and comprehensive. It includes everything you need to know to get up to speed with XML development quickly and painlessly. Jacobs begins by presenting an overview of XMLits syntax, rules, vocabularies, and the hows and whys of validity. She also covers the current state of XML support in todays web browsers. Next, Jacobs covers all of the basic essential uses of XML. You'll learn how to display XML data using CSS, and transform XML data using XSLT. You'll even learn about dynamic XML scripting using the XML DOM. The last part of the book covers advanced server-side XML uses in real-world applications, including displaying XML data in Flash, and XML-driven PHP and ASP.NET applications. And last but not least, Jacobs provides a perfect introduction to Ajax development.